Kinetic analysis of volleyball spike jump among young female volleyball players - Slovak, L.; Zahradnik, D.; Farana, R.; Svoboda, Z.; Alaei, F.; Sarvestan, J. (International Journal of Performance Analysis in Sport, 2022)
This study investigated the differences between force-time (F-T) curve variables of volleyball spike jumps (SpJ) in simulated real-game conditions, including timing, force measurements, velocity, and power among four groups of young sub-elite female volleyball players (Under-14, -16, -18 and -20). The 1-way ANOVA revealed that U-18 and U-20 players produced significantly higher values of relative peak rate of force development (p = 0.015), average rate of force development (p = 0.046), relative power (p = 0.005), peak velocity (p = 0.001) and ultimate jump heights (p = 0.001), in comparison with U-14 and U-16 peers. Correlation analysis showed a significant correlation between the relative peak rate of force development, relative average rate of force development, and relative peak power with SpJ jump height in all age groups. Time series analysis of relative applied peak forces indicated that the U-18 and U-20 players reached their relative maximum applied forces significantly earlier than U-14 and U-16 players (p = 0.021). This study suggests that the increase in the height of the SpJ across age groups in young female players is mainly related to achieving faster time to peak force by increased concentric jump-phase peak velocity. Therefore, the time to peak force can be considered as the significant kinetic contributor to higher SpJ height.